2016
DOI: 10.3390/nu8030126
|View full text |Cite
|
Sign up to set email alerts
|

Apple-Derived Pectin Modulates Gut Microbiota, Improves Gut Barrier Function, and Attenuates Metabolic Endotoxemia in Rats with Diet-Induced Obesity

Abstract: This study was aimed at determining potential effects of apple-derived pectin on weight gain, gut microbiota, gut barrier and metabolic endotoxemia in rat models of diet-induced obesity. The rats received a standard diet (control; Chow group; n = 8) or a high-fat diet (HFD; n = 32) for eight weeks to induce obesity. The top 50th percentile of weight-gainers were selected as diet induced obese rats. Thereafter, the Chow group continued on chow, and the diet induced obese rats were randomly divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
112
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 65 publications
(79 reference statements)
8
112
0
Order By: Relevance
“…AP activity is given as density values (pixel intensities) in duodenal enterocytes at a wavelength of 520 nm. Significantly different from control (C) group: *p < 0.05, **p < 0.01, ***p < 0.001 by Fisher's LSD test after ANOVA, # significant differences between C-P and C-PF groups obese rats fed with high-fat diet restored bacteria levels to normal ranges (11). Pectin addition alleviated metabolic endotoxemia and inflammation in obese rats (11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AP activity is given as density values (pixel intensities) in duodenal enterocytes at a wavelength of 520 nm. Significantly different from control (C) group: *p < 0.05, **p < 0.01, ***p < 0.001 by Fisher's LSD test after ANOVA, # significant differences between C-P and C-PF groups obese rats fed with high-fat diet restored bacteria levels to normal ranges (11). Pectin addition alleviated metabolic endotoxemia and inflammation in obese rats (11).…”
Section: Discussionmentioning
confidence: 97%
“…Obesity as a multifactorial disease results from interaction of genetic and environmental factors. Recent studies have demonstrated that obesity in rats is also closely related to disturbance of two dominant divisions of gut bacteria, especially increase in the Firmicutes and reduction of the Bacteroidetes (11,20). Supplementation with apple-derived pectin in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Bernard et al 19 showed that dietary pectin‐derived acidic oligosaccharides could modify the intestinal microbiota by stimulating the growth of species involved in immunity development and at the same time increased the production of butyrate and propionate. Jiang et al 20 revealed that apple‐derived pectin modulated gut microbiota in rats with diet‐induced obesity. However, the effects of dietary pectin as a protector against radiation‐induced intestinal fibrosis and its impact on radiation‐induced intestinal microbiota alteration have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…1)) (References in Table 1: Anti-cancer: Delphi et al, 2015[5]; Walia et al, 2014[28]; Schiavano et al, 2015[25]; Hung et al, 2015[10]; Li et al, 2014[21]; Kao et al, 2015[16]; Qiao et al, 2015[23]; Jedrychowski et al, 2010[12]; Le Marchand et al, 2000[19]; Anti-obesity and anti-diabetic effects: Jiang et al, 2016[14]; Sun et al, 2016[26]; Sampath et al, 2016[24]; O'Neil et al, 2015[22]; Bouderbala et al, 2016[2]; Fathy and Drees, 2016[7]; Dange and Deshpande, 2013[4]; Knekt et al, 2002[17]; Anti-inflammation: Jensen et al, 2014[13]; Espley et al, 2014[6]; Lee et al, 2014[20]; Hepato-protective: Cheng et al, 2014[3]; Krajka-Kuźniak et al, 2015[18]; Antigenotoxicity: Gomes de Moura et al, 2015[8]; Reduction of cardiotoxicity: Vineetha et al, 2014[27]; Etc. : Hodgson et al, 2016[9]).…”
mentioning
confidence: 99%